A study on the properties of oil palm mesocarp fiber-reinforced bioplastic - Tan, Kok Zhuan (2017)
About 10.3 million tonnes of mesocarp fibre are produced annually yet are not utilise properly. In agriculture industry, biodegradable plastics are desirable alternative to the current black low density poly( ethylene) plastic. Therefore, a research on bio-polybag was carried out with the objectives to utilize agricultural biomass for the production of biodegradable polybag and to investigate the properties of obtained polybag in terms of mechanical properties, surface structure, and biodegradability. In our research, Oil Palm Mesocarp Fibre (OPMF) was used due to its great abundance in Malaysia. Polylactic Acid (PLA) was then added and mixed with the OPMF in different ratio to produce bio-polybag. Three main tests which were tensile strength test, Scanning Election Microscopy and accelerated aging test, were carried out to study the morphology and mechanical properties of the bio-polybag. Based on the results obtained, 50wt% OPMF/50wt% PLA was chosen to be the optimum ratio in bio-polybag production due to tensile strength of 8.1 MPa, elongation at break at 2.2%, tensile modulus at 368.18MPa, decomposite rate of 2.88% and SEM test shows many voids and gaps yet with maximum used of biomass material. Hence, 50% OPMF is the most suitable biomass to use as biodegradable polybag.